Long-term resilience of late holocene coastal subsistence system in Southeastern South america. - André Carlo Colonese; Matthew Collins; Alexandre Lucquin; Michael Eustace; Y Hancock; Raquel de Almeida Rocha Ponzoni; Alice Mora; Colin Smith; Paulo Deblasis; Levy Figuti; Veronica Wesolowski; Claudia Regina Plens; et al. (PLoS ONE)
Isotopic and molecular analysis on human, fauna and pottery remains can provide valuable new insights into the diets and subsistence practices of prehistoric populations. These are crucial to elucidate the resilience of social-ecological systems to cultural and environmental change. Bulk collagen carbon and nitrogen isotopic analysis of 82 human individuals from mid to late Holocene Brazilian archaeological sites (∼6,700 to ∼1,000 cal BP) reveal an adequate protein incorporation and, on the coast, the continuation in subsistence strategies based on the exploitation of aquatic resources despite the introduction of pottery and domesticated plant foods. These results are supported by carbon isotope analysis of single amino acid extracted from bone collagen. Chemical and isotopic analysis also shows that pottery technology was used to process marine foods and therefore assimilated into the existing subsistence strategy. Our multidisciplinary results demonstrate the resilient character of the coastal economy to cultural change during the late Holocene in southern Brazil.